Transmedia storytelling during the COVID-19 pandemic: Marvel’s WandaVision and Zack Snyder’s Justice League - Webster, Luke; Leaver, Tama; Sandry, Eleanor (University of Illinois at Chicago Library, 2022)
The COVID-19 pandemic accelerated the importance of streaming within the context of commercial transmedia strategies. While cinemas have remained closed, studios have used streaming to extend audience engagement, and experiment with transmedia strategies attached to large intellectual properties. This paper seeks to determine how the pandemic affected transmedia and a shift to streaming. Drawing from key scholarly transmedia theory, and industry insights into transmedia best practice, this paper analyses the release of Marvel’s WandaVision and Zack Snyder’s Justice League and maps them against the larger transmedia strategies being used by Disney and Warner Bros. to create the Marvel Cinematic Universe (MCU) and DC Extended Universe (DCEU), respectively. This research demonstrates that streaming has become the critical component of commercial transmedia. Marvel are using streaming to enhance the integrity of one consistent storyworld. DC are placing greater priority on character than storyworld and using streaming to create a multiverse experience with divergent authorial voices. These varied styles of transmedia storytelling can be attributed to the organisational structures of each parent company, as well as the comic book source material. The pandemic created an opportunity to observe the amplified audience reactions to each approach. As streaming platforms occupy a greater role in transmedia scholarship, these findings will assist in the development of longitudinal research that explores the transformative impact of streaming on commercial transmedia entertainment.